Metabolic characteristics of intracellular trehalose enrichment in salt-tolerant Zygosaccharomyces rouxii - Wei, Yangjian; Yan, Zhenzhen; Liu, Mengqi; Chen, Dunwu; Chen, Xiong; Li, Xin (Frontiers in Microbiology, 2022)
The salt-tolerant flavor yeast Zygosaccharomyces rouxii is an important food flavor microorganism, but its intracellular stress-resistant trehalose synthesis efficiency has been shown to be low, resulting in its weak high-temperature resistance. Using a previously established feeding and heat shock-coupled fermentation regulation strategy that effectively induces intracellular trehalose synthesis and accumulation of Z. rouxii in a 20 L mechanically stirred ventilated fermenter, the intracellular and extracellular levels of carbohydrates, organic acids, and amino acids were analyzed using metabolomics research methods. Our results showed that glucose supplementation could promote the growth of yeast cells, but high temperatures (> 35°C) significantly prevented cell growth. Under three different growth strategies, extracellular glucose was continuously utilized and intracellular glucose was continuously metabolized, but glucose overflow metabolism was inhibited by high temperature, which showed that the level of extracellular ethanol was stable. High temperature stimulated significant intracellular trehalose accumulation (c20.5h = 80.78 mg/g DCW) but not efflux, while xylitol accumulated (c20.5h = 185.97 mg/g DCW) and was effluxed (c20.5h = 29.78 g/L). Moreover, heat resistance evaluation showed that xylitol and trehalose had heat-protective effects on Z. rouxii. Additionally, a large amount of propionic acid and butyric acid accumulated inside and outside these cells, showing that the conversion of glucose to acid in yeast cells becomes the main pathway of glucose overflow metabolism in high temperatures. In addition, the increased demand of yeast cells for phenylalanine, threonine, and glycine at high temperatures suggested that these metabolites participated in the temperature adaptation of Z. rouxii in different ways. Valine, leucine/isoleucine (Branched Chain Amino Acids or BCAAs) were mainly affected by the addition of glucose, while glucose, sucrose, aspartic acid/asparagine, and glutamate/glutamine were not affected by this temperature regulation as a whole. This study could help deepen our understanding of the high-temperature adaptation mechanism of salt-tolerant Z. rouxii, and has theoretical significance for the application of highly tolerant yeast to food brewing.